2021
DOI: 10.1186/s12889-021-12138-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and self-efficacy beliefs for healthy eating and physical activity among Arabic-speaking university students: adaptation and implementation of health beliefs survey questionnaire

Abstract: Background Few assessment tools exist for investigating perceived social support and self-efficacy behaviors in Arabic-speaking populations. Moreover, literature on the levels of social support and self-efficacy for adopting healthy eating and engaging in regular physical activity among Arabic-speaking young adults is currently lacking. This study aimed to adapt the Health Beliefs Survey Questionnaire (HBSQ) for Arabic-speaking populations and assess perceived social support and self-efficacy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(55 reference statements)
2
4
0
Order By: Relevance
“…The mean for the total healthy eating self-efficacy was 2.28, showing a low degree of healthy-eating selfefficacy among students; this indicates that they do not have the capacity and belief in their commitment to healthful eating, and they cannot regulate themselves and their thoughts about healthy eating in terms of the quality of excellent and nutritious food; this may be due to a lack of nutrition knowledge. This conclusion is consistent with [59] findings indicating undergraduates in the United Arab Emirates have low self-efficacy towards healthy eating.…”
Section: The Intensity Use Of Mhealth Applications Nutrition Knowledg...supporting
confidence: 92%
See 1 more Smart Citation
“…The mean for the total healthy eating self-efficacy was 2.28, showing a low degree of healthy-eating selfefficacy among students; this indicates that they do not have the capacity and belief in their commitment to healthful eating, and they cannot regulate themselves and their thoughts about healthy eating in terms of the quality of excellent and nutritious food; this may be due to a lack of nutrition knowledge. This conclusion is consistent with [59] findings indicating undergraduates in the United Arab Emirates have low self-efficacy towards healthy eating.…”
Section: The Intensity Use Of Mhealth Applications Nutrition Knowledg...supporting
confidence: 92%
“…In conclusion, healthy eating self-efficacy plays a significant role in people's health because it impacts the individual food choice and dietary intake, which are connected to an individual's health; nevertheless, a lack of recently completed research aiming to assess the degree of healthy eating self-efficacy among undergraduates using sophisticated measures rather than a perspective questionnaire, the one we found was of Habiba and, his team [59] who did a study among undergraduates has been discovered.…”
Section: Mhealth Apps and Healthy Eating Self-efficacymentioning
confidence: 83%
“…For instance, an empirical study investigated a group of American cancer survivors and found that less self-efficacy was associated with more severe depressive symptoms [74], whereas another study reported that participation in training programs aimed at improving self-efficacy significantly decreased the depression scores of pregnant women in Iran [81]. In addition, some studies suggested that self-efficacy can also be affected by interpersonal processes, such as social interaction and social support [82][83][84][85]. For example, Siciliano argued that self-efficacy can be strengthened by relevant knowledge and beliefs accessed from the individual's social network [86].…”
Section: Perceived Social Support Emotion-regulation Difficulties Sel...mentioning
confidence: 99%
“…As college students become more independent, some personal characteristics and interpersonal influences begin to serve important roles and have specific relevance to the formation of healthy behaviors, relative to that which they served in other life stages, including: (1) psychosocial characteristics (e.g., self-efficacy) being developed or established during emerging adulthood; (2) body shape-related belief due to the greater attention to body shape [ 10 ]; and (3) peer support because of spending more time with peers and less time with family [ 11 ]. According to the SCT, self-efficacy and health belief (e.g., body shape-related belief) contribute towards overcoming the barriers to adopt and maintain health behaviors [ 9 ], with higher levels being associated with higher intakes of fruit and vegetables [ 12 ], calcium and vitamin D [ 13 ], lower intakes of high-calorie food [ 14 ], and more engagement in PA [ 15 ]. Interpersonal factors, such as peer support, are also very important in shaping individual behaviors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%